Dis/abled Childhoods? A Transdisciplinary Approach (Springer International Publishing, 2018)
This edited collection explores the intersectionality of childhood and disability. Whereas available scholarship tends to concentrate on care-giving, parenting, or supporting and teaching children and young people with special educational needs and disabilities, the contributors to this collection offer an engaging and accessible insight into childhoods that are impacted by disability and impairment. The discussions cut across traditional disciplinary divides and offer critical insights into the key issues that relate to disabled children and young people's lives, encouraging the exploration of both disability and childhoods in their broadest terms. Dis/abled Childhoods? will be of interest to students and scholars across a range of disciplines including Special Educational Needs; Childhood Studies; Disability Studies; Youth Studies; and Health and Social Care.